EEG oscillatory signatures of increased cognitive control at intersections: a virtual reality driving simulation - Senftleben, Ulrike; Kessler, Klaus (Frontiers in Virtual Reality, 2024)
Intersections are particularly complex traffic situations and are often the scene of accidents. Driver behaviour and decision-making might be affected by specific factors such as the right of way, traffic volume, and the occurrence of a critical event directly before the intersection. Here, we developed a new driving scenario to test the impact of these factors in virtual reality using a fully immersive head-mounted display. Participants had to navigate through a series of intersections to reach their target destination. We recorded their driving behaviour as well as their brain activity using electroencephalography. Our results showed that participants proactively engaged cognitive control processes when approaching an intersection with high traffic volume and when reacting to a critical event, as indexed by increased theta power. We did not find differences for right of way. We further discuss advantages and potential challenges of a VR-based approach to driving simulations.